Impact of neoadjuvant chemoradiotherapy on the local recurrence and distant metastasis pattern of locally advanced rectal cancer: a propensity score-matched analysis. Issue 18 (20th September 2021) - Yu, Liang; Xu, Tian-Lei; Zhang, Lin; Shen, Shuo-Hao; Zhu, Yue-Lu; Fang, Hui; Zhang, Hai-Zeng
Abstract: Background: Previous studies have demonstrated different predominant sites of distant metastasis between patients with and without neoadjuvant chemoradiotherapy (NCRT). This study aimed to explore whether NCRT could influence the metastasis pattern of rectal cancer through a propensity score-matched analysis. Methods: In total, 1296 patients with NCRT or post-operative chemoradiotherapy (PCRT) were enrolled in this study between January 2008 and December 2015. Propensity score matching was used to correct for differences in baseline characteristics between the two groups. After propensity score matching, the metastasis pattern, including metastasis sites and timing, was compared and analyzed. Results: After propensity score matching, there were 408 patients in the PCRT group and 245 patients in the NCRT group. NCRT significantly reduced local recurrence (4.1% vs. 10.3%, P  = 0.004), but not distant metastases (28.2% vs . 27.9%, P  = 0.924) compared with PCRT. In both the NCRT and PCRT groups, the most common metastasis site was the lung, followed by the liver. The NCRT group developed local recurrence and distant metastases later than the PCRT group (median time: 29.2 [18.8, 52.0] months vs . 18.7 [13.3, 30.0] months, Z  = –2.342, P  = 0.019; and 21.2 [12.2, 33.8] vs . 16.4 [9.3, 27.9] months, Z  = –1.765, P  = 0.035, respectively). The distant metastases occurred mainly in the 2nd year after surgery in both the PCRT group (39/114, 34.2%) and NCRT group (21/69, 30.4%). However, 20.3% (14/69) of the distant metastases appeared in the 3rd year in the NCRT group, while this number was only 13.2% (15/114) in the PCRT group. Conclusions: The predominant site of distant metastases was the lung, followed by the liver, for both the NCRT group and PCRT group. NCRT did not influence the predominant site of distant metastases, but the NCRT group developed local recurrence and distant metastases later than the PCRT group. The follow-up strategy for patients with NCRT should be adjusted and a longer intensive follow-up is needed.